Crime Prevention and Community: Operationalizing the Concept of Community in the City of Ottawa's Community Development Framework - Dunbar, Laura Kristen (University of Ottawa (Canada), 2010)
The 'community' has become one of the focal points of how crime prevention and community safety issues are addressed in Canada. However, empirical research has demonstrated that crime prevention programs delivered at the community level have generally fallen short of their promises. This suggests that the community and strategies of community mobilization have been used in crime prevention without a clear understanding of the meaning of the concept. A qualitative case study of the City of Ottawa's Community Development Framework serves to illustrate how the concept of community is translated into practice, and reveals the gaps between conceptions of what community ought to be and the 'messy actualities' of community-based practices. It concludes that a greater appreciation of communities and their particular capabilities should help inform the development and implementation of crime prevention strategies and initiatives in the local context.
Keywords: Sociology, Criminology and Penology.